Antiphospholipid antibodies bind syncytiotrophoblast mitochondria and alter the proteome of extruded syncytial nuclear aggregates. Issue 12 (December 2015) - Pantham, Priyadarshini; Viall, Chez A.; Chen, Qi; Kleffmann, Torsten; Print, Cristin G.; Chamley, Lawrence W.
Abstract: Introduction: Antiphospholipid antibodies (aPL) are autoantibodies that increase the risk of women developing the hypertensive disorder pre-eclampsia. aPL are internalised by the syncytiotrophoblast and increase extrusion of necrotic multinucleated syncytial nuclear aggregates (SNAs), which may trigger endothelial dysfunction in pre-eclampsia. The mechanisms by which aPL alter death processes in the syncytiotrophoblast leading to extrusion of SNAs are unknown. Methods: First trimester human placentae (n = 10) were dissected into explants and cultured either with aPL (50 μg/mL), isotype-matched control antibody (50 μg/mL), or media for 24 h. Harvested SNAs underwent iTRAQ proteomic analysis. Mitochondria in syncytiotrophoblast treated with aPL labelled with FluoroNanogold were visualised using transmission electron microscopy (TEM). Results: aPL altered the expression of 72 proteins in SNAs. Thirteen proteins were involved in mitochondrial function. TEM demonstrated that aPL bind to mitochondria in the syncytiotrophoblast and may cause mitochondrial swelling. Discussion: aPL disrupt mitochondria increasing the extrusion of SNAs with an altered proteome from the syncytiotrophoblast. These altered SNAs may trigger endothelial dysfunction and pre-eclampsia in these pregnancies. Highlights: We examine the effect of antiphospholipid antibodies (aPL) on placental death. aPL increase extrusion of syncytial nuclear aggregates (SNAs) from placentae. 13 mitochondria-associated proteins were altered by aPL in SNAs. aPL bind to syncytiotrophoblast mitochondria and cause swelling. Mitochondrial dysfunction caused by aPL alters placental death processes.